Comparative study of bupivacaine and bupivacaine plus dexamethasone under ultrasound guidance for sacral erector plane block in pediatric urological surgeries (Pain medicine, 2025)
BACKGROUND: sacral erecter spinae plane block is a relatively new and safe interfascial plane block for paediatric urogenital surgeries. We aimed at comparing the intraoperative and postoperative analgesic efficacy of Bupivacaine alone and Bupivacaine plus Dexamethasone in ultrasonography guided single shot sacral erecter spinae plane block for urogenital surgeries in paediatric patients under general anaesthesia.METHODS: 30 patients, ASA 1 / 2,  12 months – 12 years undergoing urogenital surgeries were randomly divided into 2 groups. Under  general anaesthesia, in prone position, with  linear ultrasound probe placed longitudinally in the midline; 25 G, 90 mm spinal needle was advanced  craniocaudally  until its tip reached  the 4th sacral crest and prepared drug was injected Group A received 1ml/kg of 0.25% Bupivacaine with 2ml salineGroup B received 1 ml/kg of 0.25% Bupivacaine with 0.2mg/kg Dexamethasone in saline to make total volume of 2 ml.RESULTS:  All  patients remained haemodynamically stable intraoperatively in both groups with comparable duration of analgesia postoperatively. Also, the difference in mean FLACC R score upto 24 hours postoperatively was not significant between the two groups and no side effects were reported.CONCLUSION: The addition of Dexamethasone to Bupivacaine in ultrasonography guided single shot sacral erecter spinae plane block for urogenital surgeries in paediatric patients under general anaesthesia neither modified the analgesic efficacy of Bupivacaine intraoperatively nor did it significantly prolong the duration of analgesia postoperatively.
Keywords: Sacral erector spinae plane block; fascial plane block; ultrasonography; bupivacaine; dexamethasone